Respuesta :
Question restated.
which is not equivalent to d = rt?
r = t/d
r = d/t
t = d/r
d = tr
If we divide both sides of the original equation by t, we are left with r = d/t, so we know that this is true. if we compare this, however, with the first item on the list, we can see that t/d does not equal d/t, so the first item on the list is the wrong one.
which is not equivalent to d = rt?
r = t/d
r = d/t
t = d/r
d = tr
If we divide both sides of the original equation by t, we are left with r = d/t, so we know that this is true. if we compare this, however, with the first item on the list, we can see that t/d does not equal d/t, so the first item on the list is the wrong one.
Answer:
r = t/d
Step-by-step explanation:
hope this helps :3